IMPLEMENTATION OF THE MERDEKA CURRICULUM IN GEOGRAPHY SUBJECT IN BANDA ACEH CITY - Mirza Desfandi; Utia Rahmah; Ahmad Nubli Gadeng (Universitas Sebelas Maret (UNS), 2025)
This research aims to determine how the implementation of the merdeka curriculum in geography subjects in Banda Aceh City. This study used a survey technique which was carried out in 10 schools for geography teachers in Banda Aceh City. Data were collected through interviews, observations, documentation studies and questionnaires. Data were analyzed using descriptive statistics. From this research it is known that the implementation of the independence curriculum in Banda Aceh are the neutral/sufficient category of 38.75%, the Less Good category of 27.9%, and the Very Less Good category of 0.26%, then those who answered always and often were 70.55%, according to the category of percentage criteria for interpretation of scores, thus from this study it can be concluded that teachers have succeeded in implementing the merdea curriculum in geography subjects in high schools throughout Banda Aceh City.